2014
DOI: 10.1080/01652176.2014.909960
|View full text |Cite
|
Sign up to set email alerts
|

Neglected leptospirosis in raccoons (Procyon lotor) in Indiana, USA

Abstract: Background: Leptospirosis is a globally important zoonotic disease occurring clinically and subclinically in humans and animals. Objectives: To determine whether raccoons in Indiana carried leptospires in their kidneys. Animals and methods: Thirty-four raccoons were live-trapped from two forest patches in central Indiana. Following euthanasia, a portion of kidney (2 cm 2 ) from each raccoon was homogenized and used for leptospiral culture. Leptospiral cultures were subjected to DNA extraction and various polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…Our results show that raccoons are competent, peridomestic wildlife hosts for Leptospira in urban areas of Costa Rica. The identified Leptospira prevalence (32.6%) in Costa Rica is consistent with studies in temperate zones performed by Jardine et al (2011a) and Duncan et al (2012), who reported similar findings (30%), and is consistent with other studies, where prevalence ranged from 10% to 70% (Mitchell et al, 1999, Hamir et al, 2001, Richardson and Gauthier, 2003, Bischof and Rogers, 2005, Junge et al, 2007, Koizumi et al, 2009, Raizman et al, 2009, Jardine et al, 2011b, Tan et al, 2014. However, to date, no data were available for the prevalence of Leptospira in raccoons in a Mesoamerican country.…”
Section: Leptospirasupporting
confidence: 88%
“…Our results show that raccoons are competent, peridomestic wildlife hosts for Leptospira in urban areas of Costa Rica. The identified Leptospira prevalence (32.6%) in Costa Rica is consistent with studies in temperate zones performed by Jardine et al (2011a) and Duncan et al (2012), who reported similar findings (30%), and is consistent with other studies, where prevalence ranged from 10% to 70% (Mitchell et al, 1999, Hamir et al, 2001, Richardson and Gauthier, 2003, Bischof and Rogers, 2005, Junge et al, 2007, Koizumi et al, 2009, Raizman et al, 2009, Jardine et al, 2011b, Tan et al, 2014. However, to date, no data were available for the prevalence of Leptospira in raccoons in a Mesoamerican country.…”
Section: Leptospirasupporting
confidence: 88%
“…Shearer et al (2014) detected leptospires by IHC in renal tissue from 42% of 33 skunks and 33% of 245 raccoons in Ontario, Canada and Duncan et al (2012) found 30% of 65 raccoons in Colorado to be positive for renal leptospires by IHC. We found a higher renal PCR-prevalence in California skunks than the 18% (n = 49) that was detected recently in British Columbia, Canada (Britton et al 2017) but a substantially lower rate of infection than was found in raccoons in Indiana where 100% of 34 raccoons from two sites were culture positive for renal leptospires (Tan et al 2014).…”
Section: Discussioncontrasting
confidence: 44%
“…infects over 160 domestic and wild animal species worldwide (Babudieri 1958, Matthias et al 2008, Ko et al 2009. Clinical leptospirosis in humans and dogs ranges and Rogers 2005, Raizman et al 2009, Allen et al 2014, and active infection was reported in these regions as well (Roth et al 1963, Shearer et al 2014, Tan et al 2014). However, their roles in leptospirosis in western North America were poorly documented (Duncan et al 2012, Britton et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Because wildlife in a natural setting are not vaccinated, we used a cutoff titer 1:25 for detection of exposure to Leptospira. A study using a cutoff of 1:40 reported 46.1% seroprevalence in raccoons at titers 1:80 (Tan et al 2014). Our seroprevalence in raccoons was 54.8%, comparable to 47% in Indiana (Raizman et al 2009), 48% in Illinois (Mitchell et al 1999), and 36% in Connecticut (Richardson and Gauthier 2003); but higher than 11% in Nebraska (Bischof and Rogers 2005).…”
Section: Discussionmentioning
confidence: 40%